PERAN PEMERINTAH DALAM PENGEMBANGAN OBJEK WISATA AIR TERJUN SUNGAI MURAI DI KELURAHAN ROKAN, KECAMATAN ROKAN IV KOTO, ROKAN HULU - Sofyan Hadi; Adip Nas Ijlal; A. Farhan; Annisa Zaari Amni; Atikah Nandini; Humay Arsyakinah Tanjung; Pikri Wahyudi; Putri Oktaviani; Rema Sepmawati; Rizki Lestari; Selvi Pebriani (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
The purpose of this journal is to provide broader knowledge related to efforts to preserve and develop local tourism objects, namely Sungai Murai Waterfall so that tourists and the surrounding community can enjoy it as a natural recreation area. The government of Rokan Hulu Regency explores all the potentials it has and requires local governments to administer governance and develop regional potential. The first step that can be taken by local governments is to see the potentials they have and be able to manage them well and fight for them. The activity carried out by the UNRI 2022 Kukerta students in the form of installing a signboard "MURAI SUNGAI WATERFALL TOURISM OBJECT" which has been prepared so that visitors will know that there is a tourist attraction, then students also carry out Gotong Royong cleaning the Waterfall area so that it looks beautiful, and the naturalness of the water is maintained. The waterfall, and the last activity is to make Google Maps as directions for Sungai Murai Waterfall so that visitors from various regions can easily find the location because basically people like to visit tourist objects that are easy to find.